Analisis Implementasi Komunikasi Modbus TCP/IP dalam Penerapan Visualisasi Data Hasil Produksi pada Sistem Andon Line Production : Analysis of the Implementation of Modbus TCP/IP Communication in the Application of Production Data Visualization in the Andon Line Production System - Bonanza Yoma Pratama; Efi Anisa (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2023)
Andon refers to an information system aimed at management, maintenance, planners, or other workers regarding quality, process, or quantity issues. To support accurate data communication, a reliable protocol and high precision are required. The Modbus TCP/IP protocol is compatible with Andon systems. This study aims to analyze the implementation of Modbus TCP/IP communication in the application of production data visualization in online production systems. At a certain distance, the antenna's data must display the data's precision in real time. The average data transfer time at the farthest distance tested, 50 meters, was 0.0043 seconds, indicating that the longer the distance between the client and server, the longer the waiting time tends to be, but does not exceed 0.01 seconds if it does not affect production activities. These results are still pertinent to the information required by the organization.